Cushioning mechanism of the metatarsals during landing for the skateboarding ollie maneuver - Wu, Yusen; Wang, Haichun; Deng, Cheng; Guo, Yangyu; Zhu, Xiaolan (Frontiers in Bioengineering and Biotechnology, 2024)
Skateboarding is an Olympic event with frequent jumping and landing, where the cushioning effect by the foot structure (from the arch, metatarsals, etc.) and damping performance by sports equipment (shoes, insoles, etc.) can greatly affect an athlete’s sports performance and lower the risk of limb injury. Skateboarding is characterized by the formation of a “man–shoe–skateboard system,” which makes its foot cushioning mechanism different from those of other sports maneuvers, such as basketball vertical jump and gymnastics broad jump. Therefore, it is necessary to clarify the cushioning mechanism of the foot structure upon landing on a skateboard. To achieve this, a multibody finite element model of the right foot, shoe, and skateboard was created using Mimics, Geomagic, and ANSYS. Kinetic data from the ollie maneuver were used to determine the plantar pressure and Achilles tendon force at three characteristics (T1, T2, and T3). The stress and strain on the foot and metatarsals (MT1–5) were then simulated. The simulation results had an error of 6.98% compared to actual measurements. During landing, the force exerted on the internal soft tissues tends to increase. The stress and strain variations were highest on MT2, MT3, and MT4. Moreover, the torsion angle of MT1 was greater than those of the other metatarsals. Additionally, the displacements of MT2, MT3, and MT4 were higher than those of the other parts. This research shows that skateboarders need to absorb the ground reaction force through the movements of the MTs for ollie landing. The soft tissues, bones, and ligaments in the front foot may have high risks of injury. The developed model serves as a valuable tool for analyzing the foot mechanisms in skateboarding; furthermore, it is crucial to enhance cushioning for the front foot during the design of skateboard shoes to reduce potential injuries.